Relevansi Hukum Adat Himpun Satempap Sajari Terhadap Kemaslahatan Perkawinan Masyarakat Melayu Jambi: Perspektif Najmuddin At-Thufi - M. Ilham Kholiq; Roibin Roibin; Khoirul Hidayah (Fakultas Syariah dan Ekonomi Islam, Universitas Ibrahimy, 2026)
This study examines the implementation of the Himpun Satempap Sajari customary tradition in Malay marriage practices in Muaro Tabun Village, VII Koto District, Tebo Regency, Jambi Province, and analyzes it from the perspective of Najmuddin At-Thufi’s concept of maslahah. The study aims to describe the stages, functions, and social relevance of the tradition in contemporary society. This research employs an empirical legal research method using a field research approach. Data were collected through observation, interviews with customary leaders, religious figures, and community members, as well as documentation studies. The data were analyzed using the interactive analysis model of Miles and Huberman, including data reduction, data presentation, and conclusion verification. The findings indicate that Himpun Satempap Sajari consists of several stages, namely Baangkat Bapak, Ngantar Tando, Himpun Ahli Waris, Himpun Sanagari, and Pasang Patauh. These traditions reflect values of solidarity, mutual cooperation, deliberation, and social harmony. From the perspective of Najmuddin At-Thufi’s maslahah theory, the tradition contains social benefits because it strengthens kinship and social relations within the community. However, excessive economic burdens and social sanctions may potentially create social hardship for certain families. Therefore, the implementation of customary practices should prioritize public welfare and adjust to contemporary socio-economic conditions.